Relação entre força muscular e lesão no ombro de praticantes de voleibol - Lima, Alane Almeida (2022)
Volleyball is one of the most practiced sports in the world and its practitioners have a high prevalence of shoulder pain. The repeatedly executed serve and attack gestures require large ranges of motion and exert high impact force on the joint predisposing to injury. Due to the low anatomical stability of the shoulder joint, in addition to the important role in the production of force and power during the gesture, the musculature is also essential in the stability of the joint. However, literature is conflicting about the relationship between strength and injury in volleyball players. Therefore, the aim of our study was to identify the state of art of studies on the relationship between muscle strength and shoulder injury in volleyball players. For that a Systematic Review of the literature was carry out in four electronic databases: PubMed, Web of Science, SPORTDiscus and Scopus in June 2022. Fifteen studies were included in this review. Alone, muscle strength were not found as a risk factor for the development of shoulder injury, as well as there was no difference in isokinetic muscle strength. However, there is limited evidence suggesting that eccentric force can prevent and reduce the incidence of shoulder injuries. Future studies should consider muscle strength associated with other factors for a better understanding of the risks for shoulder injury in volleyball players. Association was found between weak external rotators and shoulder abductors and infraspinatus atrophy (moderate evidence), as well as weak trunk muscle resistance and anterior shoulder instability (limited evidence), but further studies are needed to verify whether these relationships are causes or consequences of the injury. We also found that strengthening the scapula muscles can reduce pain and improve the strength of the shoulder's external rotators (limited evidence). Based on findings to date, muscle strength assessment appears to be relevant only in screening for asymptomatic infraspinatus atrophy. Due to the limited evidence available, the sports team should exercise caution when suggest eccentric strengthening of shoulder rotators in order to reduce the incidence of injury, when evaluating trunk musculature in practitioners with anterior shoulder instability and when suggest scapula muscle strengthening in practitioners with injury- associated scapular dyskinesis.